THE EFFECT OF THE “RAYQAL” APPLICATION ON MOTHERS’ KNOWLEDGE, ATTITUDE, AND BEHAVIOR IN STIMULATING TODDLER DEVELOPMENT - Harefa, Umy Darni; Herawati, Yanti; Rachmiatie, Atie; Garna, Herry; Anwar, Anita Deborah; Wijayanegara, Hidayat (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Parents need effective media to enhance their knowledge, attitudes, and behaviors in supporting early childhood growth and development. One such tool is the